Heterotopic Xenotransplation of Newborn Piglet Aortic Fragments After Hypothermal Incubation in Preservation Solutions - Bohuslavskyi, Konstantin I.; Alabedalkarim, Natalia M.; Gvozdyuk, Yana V.; Padalko, Vladimir I.; Remnyova, Natalia O.; Protsenko, Olena S.; Bozhok, Galina A. (Problems of Cryobiology and Cryomedicine, 2019)
Nowadays the porcine vessels and heart valves have been widely applied in transplantology. Due to a high level of Gal-α-1,3-Gal (α-Gal epitope) expression, the porcine bioprostheses are specially treated prior to transplantation either to remove this epitope or to deactivate it. Our previous findings showed that certain media, used for hypothermic storage (HS), reduced the α-Gal epitope expression in aortic tissue in vitro. Here, we studied the HS impact in the histidine-tryptophan-ketoglutarate (HTK), Euro-Collins and Dulbecco’s Modified Eagle Medium (DMEM) solutions on aortic graft integrity in vivo. The analysis of aortic wall histological structure and the evaluation of the immunoproteasome subunits LMP2 and LMP7 expression level demonstrated the aortic fragments, subjected to HS in Euro-Collins solution to day 7 after xenotransplantation to cause a less pronounced immune response as compared to the HTK- and DMEM-incubated xenografts. This may be partially due to the Euro-Collins medium composition. Our findings may be of interest for ela-borating the novel methods for donor material pre-transplantation preparation. Probl Cryobiol Cryomed 2019; 29(1): 073–087